Implementation of landscape design as elements in creating values for housing areas in Klang Valley, Malaysia - Mohd Shahli, FitryNadia; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zaidin, Nurbazliah (TuEngr.com Group, 2015)
as one of the indicators for making a value to the house has never been important. Subsequently, enhancement of the quality of life and sustain a livable environment for future development seems crucial and related to the values of housing area. Therefore, this paper is aimed to identify the contribution of landscape design as an element in influencing the values of housing area in urban areas. The method specifically adopts questionnaires survey, interview and observation technique that conducted in the selected housing area in Klang Valley. The findings show the involvement of landscape design in term of its planning, characteristic and elements can influence the value of the house. It is hoped that this paper may provide significant information on the implication of landscape design towards influencing the values of the house and also attract prospect buyers in the future.